Evaluation of Insects that Exploit Temporary Protein Resources Emphasizing the Action of Ants (Hymenoptera, Formicidae) in a Neotropical Semi-deciduous Forest - Luiz Carlos Santos-Junior (Universidade Estadual de Feira de Santana, 2014)
The majority of the ants is opportunistic and generalist foragers, commonly feeding on vegetable secretions, seeds, and living or dead animal material. They may be present on any type of substrate even, occasionally on carcasses. This work, then, aimed to evaluate the action of insects, especially ants, in the exploitation of protein resources in forest environment. Monthly collections were made over a year and, in each collection, were made observations during 12 consecutive hours. To simulate exposure of protein resources we used three types of baits, sardines, beef liver and chicken. To evaluate the importance of ants on protein resources for each type of bait there was a control replica with physical barrier to prevent their access. The ants were observed on all baits throughout the collection period. In total, the baits were visited by 34 species of ants. The main genus of ants to visit the baits were: Pheidole, Crematogaster and Solenopsis. These results demonstrate that the presence of ants is important to ecological succession on temporary protein sources in forest environments interfering in the occurrence of other frequent groups in this type of resource, such as flies, for instance. The species that dominated the baits, when presents, were those that regardless of size and aggressiveness, presented mass recruitment and exploited the baits with large flow of individuals Although some species that exhibit certain characteristics can locate the baits faster and eventually dominate them at some point, depending on the ants species that co-occur, the results for the sequence of colonization can be modified.